The Living Computer Museum. - Severance, Charles (Computer (00189162), 2016)
Charles Severance visits the Living Computer Museum in Seattle, Washington, to get back to his programming roots. The Web extra at https://youtu.be/ZHU4nzIsaIM goes behind the scenes of the author's recent visit to the Living Computer Museum. In the second Web extra at https://youtu.be/lnlL7cEJqtY, author Charles Severance provides an audio recording of his Computing Conversations column.